2009
DOI: 10.1534/genetics.109.104562
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Pax6 Contiguous Gene Deletions in the Mouse, Mus musculus, Identifies Regions Distinct from Pax6 Responsible for Extreme Small-Eye and Belly-Spotting Phenotypes

Abstract: In the mouse Pax6 function is critical in a dose-dependent manner for proper eye development. Pax6 contiguous gene deletions were shown to be homozygous lethal at an early embryonic stage. Heterozygotes express belly spotting and extreme microphthalmia. The eye phenotype is more severe than in heterozygous Pax6 intragenic null mutants, raising the possibility that deletions are functionally different from intragenic null mutations or that a region distinct from Pax6 included in the deletions affects eye phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 54 publications
2
6
0
2
Order By: Relevance
“…A familial case of aniridia resulting from a deletion containing PAX6 , RCN1 , and DKFZp686k1684 was reported by Zhang et al (2011). Severe visual impairment observed in the described family is compatible with the mouse phenotype reported by Favor et al (2009). Patient p9 contains a very similar deletion of the downstream flanking region of PAX6 to the family described by Zhang et al (2011).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A familial case of aniridia resulting from a deletion containing PAX6 , RCN1 , and DKFZp686k1684 was reported by Zhang et al (2011). Severe visual impairment observed in the described family is compatible with the mouse phenotype reported by Favor et al (2009). Patient p9 contains a very similar deletion of the downstream flanking region of PAX6 to the family described by Zhang et al (2011).…”
Section: Discussionsupporting
confidence: 90%
“…The RCN1 gene is a Ca 2+ binding protein, participating in the secretory pathway. Favor et al (2009) reported that mouse, containing a heterozygous deletion of the AX6 and RCN1 genes, presents an extreme microphthalmia. They suggest that RCN1 may have an influence on the eye phenotype in PAX6 contiguous gene deletions.…”
Section: Discussionmentioning
confidence: 99%
“…This creates an unnatural situation making some phenotypes frail in a way that does not reflect the biology under study and introduces extraneous variables [30, 36]. Finally, environmental variables such as cage conditions, handling practices, and even the experimenter can increase variability [3739]. Studies of the Sey allele have been conducted on numerous different bkgds and at various timepoints, often focusing on embryonic development.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Cdh1 was present exclusively on P30 relative to P14, and plays a role in cell-cell adhesions, mobility and proliferation of epithelial cells [ 48 ]. Additional proteins exclusively expressed on P3 relative to P14 include reticulocalbin-1, plexin-B2, and low-density lipoprotein receptor-related protein 2, which are involved in the development of sensory organs [ 49 ] and nervous system [ 50 , 51 ] and thus may contribute to the development of the cochlear sensory epithelium.…”
Section: Discussionmentioning
confidence: 99%